'Here be dragons': Integrating scientific data and place-based observation for environmental management. (August 2016) - Penny, Dan; Williams, Georgia; Gillespie, Josephine; Khem, Rongden
Abstract: Yeak Loam is a volcanic crater lake in Cambodia's northeastern uplands, and represents an important economic and cultural resource for local ethnic minority groups. The lake and the surrounding crater rim are currently protected as part of a community based natural resource management scheme. Despite this, development pressure remains high, and visible deterioration of the lake's water quality is of great concern for the local community, visiting tourists, and the Cambodian Ministry of Environment. In this paper we blend scientific analyses with vernacular, place-based knowledge – coherent with the critical physical geography concept – to provide an integrated understanding of water quality change over more than 50 years. We find that changes in water quality have occurred episodically and irregularly over that period. Further, we find that these events are triggered by natural biogeochemical cycles within the lake, and in this instance are unlikely to be related to the type of land use within the protected area. Highlights: Combined vernacular knowledge and instrumental data reveal the biogeochemical dynamics of a tropical crater lake. Recent episodes of water quality deterioration are linked to natural processes within the lake. Similar events have occurred episodically over the past 50 years. Deterioration of water quality related to exogenous nutrient pollution is considered unlikely at the present time.